Genetic Modification, Factory Farms, and ALF: A Focus Group Study of the Netflix Original Film Okja - Garrett M Steede; Kelsi Opat; Leah S Curren; Erica Irlbeck (Journal of Applied Communications, 2018)
Okja is a fictional Netflix original film that was released in 2017. Okja features a “super pig” that is owned by the large, agricultural company Mirando Corporation. Okja is raised by a young girl, Mija, and her grandfather in the South Korean mountains. The film climaxes when Mija and the Animal Liberation Front (ALF) narrowly save Okja and a smuggled piglet from the slaughter process. The purpose of this study was to understand how college students responded to the film. The viewers of this film included students who were majoring in a field within the agricultural college (COA) at Texas Tech University as well as students who were majoring in a field outside of agriculture (NCOA). Emergent themes from this focus group study identified the film as overdramatized and that the film misrepresented food production. Previous knowledge and experiences impacted how viewers perceived the film with COA students indicating that Okja was portrayed more like a pet than as a food animal. Both COA and NCOA students indicated that their food purchasing decisions would not be affected by viewing the film. Findings suggested that entertainment films may not be an effective method for changing public opinion of agriculture and food production. Transparency in agriculture through real-life and real-time activities in a documentary style may serve a greater role in improving public opinion of food and agricultural production practices and industries.Findings from this study serve as an indicator of the role entertainment films play in swaying public opinion of food and agriculture.
Keywords: Focus Group; Film; Genetic Modification; Qualitative; Semiotics; Food; Livestock